2011
DOI: 10.1002/lt.22342
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence in living liver donors

Abstract: All right hepatic lobe (RHL) donors in our program are asked to participate in a longitudinal quality-of-life study that begins at their evaluation and continues throughout the first postdonation year. Here we report the characteristics of donor candidates who completed the donation process despite ambivalence. In all, 183 RHL candidates consented, and 133 became donors. Ambivalent donors (ADs; n ¼ 45) identified themselves through verbal statements or written comments, or they were identified by staff during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…This suggestion warrants further research. Simpson et al suggested that ambivalence should not be the sole reason for disqualifying donor candidates and suggested that it is appropriate to consider other psychological indicators [19]. Our study also revealed that ALDs had a better mental dimension of quality of life than did PLDs during assessment stage.…”
Section: Discussionsupporting
confidence: 58%
“…This suggestion warrants further research. Simpson et al suggested that ambivalence should not be the sole reason for disqualifying donor candidates and suggested that it is appropriate to consider other psychological indicators [19]. Our study also revealed that ALDs had a better mental dimension of quality of life than did PLDs during assessment stage.…”
Section: Discussionsupporting
confidence: 58%
“…Simpson et al (10) found similar scores, whereas Togashi et al (9) noted somewhat lower scores. The hypothesis regarding the decrease of physical QOL in living donors 3 months after LLD could be confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…The donor's ambivalence may simply indicate his or her process of deliberation. Researchers also have suggested that ambivalence should not be the sole reason to reject potential donors . Therefore, the nature and the context of ambivalence also warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%